PENYUSUNAN TRAINER KIT DAYA DAN USAHA SEBAGAI ALAT PERAGA PRAKTIKUM MATA KULIAH TERMODINAMIKA - Qoriatul Fitriyah (Politeknik Caltex Riau, 2021)
The power and work trainer kit is used as one of the learning media in thermodynamics practicum. This device focuses on measuring power, work and kinetic energy. This trainer kit uses time measurement in units of second, measurement of object mass using a load cell sensor in grams, time measurement using a timer via Arduino with units of time in seconds, and measurement of distance length in centimeters. Those measurement are needed to calculate work, power, and energy. At this stage, readings will be made on the weight of the object, the distance, and the time required for the test. The data that has been obtained will be compared with the results of calculations on visual basic software. The results of the tests carried out will show that the instrument can work well.